BENTHIC DIATOM ASSEMBLAGES FROM MADEN STREAM (ELAZIG-TURKEY): AN EXAMINATION OF COMMUNITY RELATIONSHIPS AND HABITAT PREFERENCES - Yildirim, Vesile; Cetin, A. Kadri (Parlar Scientific Publications (P S P), 2016)
In this stuady, community structure of benthic diatoms in Maden Stream was studied over 1- one year period. A total of 77 taxa were identified in benthic habitats. The aim of this stuady is to describe to epipelic, epilithic, epiphytic diatom communities in Maden Stream and the diversity of species, similarity of benthic diatoms in different habitats of stream. It is clear that certain diatom taxa have microhabitat preferences. Cretoneis arcus, Frustulia vulgaris, Meridion circulare, Navicula bacillum, N. cari, N. gracilis, N. menisculus, N. tuscula, N. reinhardtti Nitzschia hungarica, Surirella robusta were recorded in epilithic habitats. Didymosphenia geminata was recorded only in epipelic habitats The abundance of diatom taxa recorded varied substantially among the habitat types. The genera Cymbella, Navicula, Nitzschia and Gomphonema comprised the most of species and were numerically bigger in most communities. Frequency, diversity and similarity of diatoms varied among habitats.
Keywords: Benthic diatoms; habitat; streams; substratum; epilithic; epipelic; epiphytic